2018
DOI: 10.1108/ijdi-12-2017-0209
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of inflation, exchange rates and the trade balance in a small economy

Abstract: Purpose The purpose of this study is to examine the temporal relationships between inflation and exchange rate changes and their implications for the trade balance in Uganda, which saw persistent trade deficits, rising inflation and disinflation episodes, as well as significant exchange-rate realignments and other liberalization measures over the sample period considered. Design/methodology/approach The short-run dynamics of the variables in question and the pattern of their long-run relationships are examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, many studies investigate the relationship between exchange rate and inflation. Some of these studies are Koldhy and Sohrabian (1990), Altınay (1996), Kamin (1997), Mihaljek and Klau (2001), Kamin and Klau (2003), Işık et al (2004), McCarthy (2007), Bhattarai (2011), Lado (2015), Monfared and Akın (2017), Yiheyis and Musila (2018), Aksu and Emsen (2018), Duman and Sağdıç (2019), İşcan and Kaygısız (2019), Tandoğan (2020) and Gazel (2020). Studies generally reveal findings that there is a significant relationship between exchange rate and inflation.…”
Section: Theoretical and Empirical Literaturementioning
confidence: 99%
“…However, many studies investigate the relationship between exchange rate and inflation. Some of these studies are Koldhy and Sohrabian (1990), Altınay (1996), Kamin (1997), Mihaljek and Klau (2001), Kamin and Klau (2003), Işık et al (2004), McCarthy (2007), Bhattarai (2011), Lado (2015), Monfared and Akın (2017), Yiheyis and Musila (2018), Aksu and Emsen (2018), Duman and Sağdıç (2019), İşcan and Kaygısız (2019), Tandoğan (2020) and Gazel (2020). Studies generally reveal findings that there is a significant relationship between exchange rate and inflation.…”
Section: Theoretical and Empirical Literaturementioning
confidence: 99%
“…In specific to the trade deficits EMU peripheral states, Sinn (2014) argued that the high rates of domestic inflation had deteriorated the competitiveness of these economies, which led to high trade deficits. However, the evidence is contrasting as a recent study by Yiheyis and Musila (2018) reported a very little effect of inflation on the trade balance. Hence, in this study, we are considering the impact of domestic inflation (GDP deflator) on US trade balance to see whether the cause of huge trade deficit is due to increase in domestic price levels, which may erode the international competitiveness of US economy.…”
Section: Determinants Of the Trade Balancementioning
confidence: 80%
“…For instance, Aron and Muellbauer (2007) showed that increased trade openness has significantly reduced the mean inflation rate and has also reduced the exchange rate pass-through into wholesale prices. Yihevis and Musila (2018) found that inflation exerts no significant effect on the trade balance.…”
Section: Regression Resultsmentioning
confidence: 96%